A comparative study of the effect of fungicides in the prevention of damping-off desease in tomato seedlings (Lycopersicon esculentum, Mill. ). - Tupaz, Glenda Arabejo
A total of 700 native tomato seeds with 92 germination were treated with 4 different fungicides namely Captan, Brassicol, Dithane M-45 and Vitrigan Blue. This was to determine and compare the degree of effectivity of theses fungicides in preventing the occurrence of damping-off disease caused by any of the fungal species of Pythium, Rhizoctonia, Fusarium and Phytophthora., The seeds were grown in 10 seed boxes ( labelled according to treatments ) for 23 days under similar environmental conditions. The percentage germination for each treatment and the percentage of damping-off in tomato seedlings were computed. The data obtained in the percentage of germmination were analyzed statistically using one way analysis of variance, followed by Duncan's Multiple Range Test. The result showed that there was no significant differences (p<0.05) on the germination rates of the treated seeds and the control. On the other hand, the data obtained from the percentage of damping-off were statistically analyzed using the Kruskal-Wallis H Test, followed by Nonparametric Multiple Comparisons. Significant differences (q>0.10) were noted between the control ( untreated seeds ) and Captan. The other treatments were not significantly different (q<0.10) from the control and from each other